Theological Study of “The Meaning of Emptying Himself” in Philippians 2:7 and Implications as an Example for Christians in Daily Life - Ester Yunita Dewi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The phrase “Emptying Himself,” by the apostle Paul addressed to the Lord Jesus in Philippians 2:7 can be interpreted in various ways. The phrase can be interpreted that when Jesus was born into the world he was like a human being in general, not divine. It can also be interpreted that Jesus was actually a human being in general who was born with a special mission like the prophets who lived in the Old Testament. The text research on “emptying oneself” is currently one of the important verses in Christian theology regarding Christology, because it describes the action of Jesus Christ who was willing to ‘empty himself’ or what is known as kenosis. The research on the text of Philippians 2:7 will be carried out by analyzing the Greek word kenosis using the literal interpretation method, namely looking for the meaning of the original language of writing, namely Greek. To support the literal interpretation, the researcher will also conduct a contextual, grammatical and historical interpretation study. The research on this text produces meanings including: Jesus gave up His divine attributes without losing the essence of His divinity, in order to become a limited human being and take on the form of a servant. This action not only shows the love and humility of Jesus, who is an example for Christians in everyday life, but also the understanding of the essence of Christ's theology.